Clinical Pharmacology of Furosemide in Neonates: A Review - Gian Maria Pacifici (MDPI AG, 2013)
Furosemide is the diuretic most used in newborn infants. It blocks the Na+-K+-2Cl− symporter in the thick ascending limb of the loop of Henle increasing urinary excretion of Na+ and Cl−. This article aimed to review the published data on the clinical pharmacology of furosemide in neonates to provide a critical, comprehensive, authoritative and, updated survey on the metabolism, pharmacokinetics, pharmacodynamics and side-effects of furosemide in neonates. The bibliographic search was performed using PubMed and EMBASE databases as search engines; January 2013 was the cutoff point. Furosemide half-life (t1/2) is 6 to 20-fold longer, clearance (Cl) is 1.2 to 14-fold smaller and volume of distribution (Vd) is 1.3 to 6-fold larger than the adult values. t1/2 shortens and Cl increases as the neonatal maturation proceeds. Continuous intravenous infusion of furosemide yields more controlled diuresis than the intermittent intravenous infusion. Furosemide may be administered by inhalation to infants with chronic lung disease to improve pulmonary mechanics. Furosemide stimulates prostaglandin E2 synthesis, a potent dilator of the patent ductus arteriosus, and the administration of furosemide to any preterm infants should be carefully weighed against the risk of precipitation of a symptomatic patent ductus arteriosus. Infants with low birthweight treated with chronic furosemide are at risk for the development of intra-renal calcifications.